Utilization of soak liquor in microbial fuel cell. (1st October 2016) - Rajeswari, S.; Vidhya, S.; Navanietha Krishnaraj, R.; Saravanan, P.; Sundarapandiyan, S.; Maruthamuthu, S.; Ponmariappan, S.; Vijayan, M.
Graphical abstract: Highlights: The usefulness of soak liquor in microbial fuel cell was explored. No additional substrate and mediator was used in the study for energy production. The energy output was studied with simple graphite plates instead of expensive electrodes. Abstract: Soak liquor is a primary effluent from tannery industry. It poses a threat to the environment and it is necessary to treat the effluent. The predominant tannery effluent bacteria were isolated, identified and used for the electricity generation. The present study investigates the use of soak liquor for the first time as a substrate for electricity generation in Microbial Fuel Cell (MFC). The high salinity and rich organic content of soak liquor increase the efficiency of MFC. Various electrochemical characterizations such as polarization curve, cyclic voltammetry, chronoamperometry, electrochemical impedance spectrometry were performed to analyse the efficacy of the soak liquor. MFC produced a maximum power density ( P max ) of 44.02 mW/m 2 with a current density 140.34 mA/m 2 . The chemical oxygen demand (COD) reduction rate was found to be 93% ± 4.7% in a cycle period of 168 h. The presence of humic acid was identified in soak liquor, which might be involved in shuttling of electrons from the microorganisms to the electrode.